51‐2: Development of In‐Plane Super‐Fast Response (ip‐SFR) LCD for VR‐HMD. Issue 1 (30th May 2018) - Katayama, Takashi; Higashida, Shinpei; Kanashima, Atsuko; Hanaoka, Kazutaka; Yoshida, Hidefumi; Shimada, Shinji
Abstract : We developed a fast‐response LCD. The fabrication process is the same as that of the conventional Fringe‐Field‐Switching mode. A diamond‐shape slit was fabricated for applying the fringe field. The response time is half that of the conventional mode. We applied the developed technology to a 2.89‐inch LCD with a resolution of 706 ppi for Head Mount Display (HMD).